Karakteristik Edible Film dari Pati Kentang (Solanum Tuberosum L.) dengan Penambahan Gliserol - Sjamsiah Sjamsiah; Jawiana Saokani; Lismawati Lismawati (Al-Kimia, 2017)
Edible film is a thin layer that serve as the packaging or upholstery as well as food that can be eaten with a product. It is packaged and can be degraded by nature. Potato starch can be used as raw material in manufacturing edible film, in which the addition of glycerol is needed as a plasticizer that function to improve the elasticity of the edible film. The goal of the research is to know the influence of glycerol concentration variation against the characteristics of edible film of starch potatoes (Solanum tuberosum L.) the parameters examined in this study i.e the physical test that includes a test of strong thickness, tensile test and present enlargement, test the solubility and organoleptic. To help figure out the data obtained in the real effect or not, is done using the SPSS Analysis Variant 1 direction or one-way ANOVA. Characteristics of edible film from potato starch with addition of glycerol with a concentration of 20%, 30% and 40% (v/v) to the value of the thickness of consecutive 0,058 mm, 0,062 mm and 0,071mm. The value of the tensile strengh i.e 0,75 N/mm2, 0,69 N/mm2 and 0,35 N/mm2. The value obtained by elongation percent 4,96%, 9,04% and 9,51% where as the value of solubility is obtained that is 19%, 21,4% and 34,6%. Application of edible films from potato starch as the packaging on candy jelly can be acceptedas alternative packaging material for food.